ROLE OF NEUROTICISM AND EXTRAVERSION FACTORS OF PERSONALITY ON LIFE SATISFACTION IN MARRIED COUPLES - Rani, Rashmi (The Scientific Temper, 2017)
The aim of the study was to elucidate the life satisfaction in relation to ‘similarity’ and ‘dissimilarity’ (from the median cut points) on neuroticism and extraversion factors of personality in married couples. For this purpose, Three hundred (300) couples with at least Graduation qualification were sampled by following multi – stage sampling procedure and were administered Hindi version of NEO Personality Inventory (NEO PI – R) and Hindi version of satisfaction with Life Scale (SWLS), and four groups of spouses: both spouses (husband and wife) scoring low (Group – 1), husband scoring low and wife scoring high (Group – 2), husband scoring high and wife scoring low (Group – 3), and both the spouses (husband and wife) scoring high (Group – 4) on neuroticism and extraversion factor of personality (from the median cut points) were screened out and the total sum of scores (the sum of the scores of husband and wife on life satisfaction as a unit) was aimed for analysis. The data were analysed by one-way ANOVA post hoc mean comparisons were made by Tukey test. Results indicated non – significant between groups effect of neuroticism similarities/dissimilarity on life satisfaction, whereas significant between groups’ effects was observed for extraversion similarities/ dissimilarity on life satisfaction. The results further indicated that high as compared to the low scorer couples on extraversion factor revealed higher life satisfaction